Noise Elimination of a Multi-tone Broadband Noise with Hybrid Helmholtz Mufflers Using a Simulated Annealing Method - CHIU, Min-Chie (Archives of Acoustics, 2012)
Noise control is essential in an enclosed machine room where the noise level has to comply withthe occupational safety and health act. In order to overcome a pure tone noise with a high peak valuethat is harmful to human hearing, a traditional reactive muffler has been used. However, the traditionalmethod for designing a reactive muffler has proven to be time-consuming and insufficient. In order toefficiently reduce the peak noise level, interest in shape optimization of a Helmholtz muffler is coming tothe forefront.Helmholtz mufflers that deal with a pure tone have been adequately researched. However, the shapeoptimization of multi-chamber Helmholtz mufflers that deal with a broadband noise hybridized withmultiple tones within a constrained space has been mostly ignored. Therefore, this study analyzes thesound transmission loss (STL) and the best optimized design for a hybrid Helmholtz muffler under a space-constrained situation. On the basis of the plane wave theory, the four-pole system matrix used to evaluatethe acoustic performance of a multi-tone hybrid Helmholtz muffler is presented. Two numerical cases foreliminating one/two tone noises emitted from a machine room using six kinds of mufflers (muffler AF)is also introduced. To find the best acoustical performance of a space-constrained muffler, a numericalassessment using a simulated annealing (SA) method is adopted. Before the SA operation can be carriedout, the accuracy of the mathematical model has been checked using the experimental data. Eliminating abroadband noise hybridized with a pure tone (130 Hz) in Case I reveals that muffler C composed of a one-chamber Helmholtz Resonator and a one-chamber dissipative element has a noise reduction of 54.9 (dB).Moreover, as indicated in Case II, muffler F, a two-chamber Helmholtz Resonator and a one-chamberdissipative element, has a noise reduction of 69.7 (dB). Obviously, the peak values of the pure tones inCase I and Case II are efficiently reduced after the muffler is added.Consequently, a successful approach in eliminating a broadband noise hybridized with multiple tonesusing optimally shaped hybrid Helmholtz mufflers and a simulated annealing method within a constrainedspace is demonstrated.